Type 2 Diabetes - Masuo, Kazuko (IntechOpen, 2013)
Type 2 diabetes is now a global serious health problem. Patients with type 2 diabetes have 2-4 times higher risk of cardiovascular and renal complications, morbidity and mortality. This book, Type 2 Diabetes, is a unique book covering the topics including pathophysiology, complications and prevention and treatments. Understanding the etiology of the onset and development of type 2 diabetes is important to prevent type 2 diabetes complications and delay the progress. The Pathophysiology section covers a wide range of mechanisms and characteristics from the micro (molecular) to the macro (neurohormonal mechanisms and the beta-cell function in the pancreas). The Complications section includes renal complications, sympathetic nervous system imbalance, atherosclerosis, and foot ulcers which are frequently observed in diabetic patients. Finally, the Prevention and Treatments section consists of non-pharmacological treatments, bariatric surgery, pharmacological therapy, and insulin therapy. The editor hopes that this book is helpful for your clinical practice and research, and this book facilitates the reduction of global burden of type 2 diabetes.